PREDICTION OF THE CONDITION OF THE CONSTANT VOLTAGE POWER NETWORK OF THE ONBOARD EQUIPMENT WITH USE OF THE METHOD OF THE LEAST SQUARES - Казак, В.; Вакарова, А.; Гладшіюк, Б.; Гладишок, Л. (Science-based technologies, 2012)
A least-squares method used to predict the power line DC-board equipment. At the least squares method provided approximate coincidence polynomial projections and predicted parameter in the measurement points with a certain accuracy.